2021
DOI: 10.1007/s12672-021-00409-6
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of transcribed lncRNA uc.291 and SWI/SNF complex in cutaneous squamous cell carcinoma

Abstract: While non-melanoma skin cancers (NMSCs) are the most common tumours in humans, only the sub-type cutaneous squamous cell carcinoma (cSCC), might become metastatic with high lethality. We have recently identified a regulatory pathway involving the lncRNA transcript uc.291 in controlling the expression of epidermal differentiation complex genes via the interaction with ACTL6A, a component of the chromatin remodelling complex SWI/SNF. Since transcribed ultra-conserved regions (T-UCRs) are expressed in normal tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Epigenetic modifications of chromatin are crucial for regulation of gene expression and are precisely regulated by a complex network of interaction between transcription factors, chromatin remodellers [ 163 ] and even non-coding RNAs [ 57 , 164 , 165 ]. Identification of genomic regulatory elements and study of epigenetic state of chromatin historically has been achieved through analyse of DNA occupancy by distinct transcription factors (TFs) and histone modifications.…”
Section: Organoids As a Model To Study Regulation Of Expressionmentioning
confidence: 99%
“…Epigenetic modifications of chromatin are crucial for regulation of gene expression and are precisely regulated by a complex network of interaction between transcription factors, chromatin remodellers [ 163 ] and even non-coding RNAs [ 57 , 164 , 165 ]. Identification of genomic regulatory elements and study of epigenetic state of chromatin historically has been achieved through analyse of DNA occupancy by distinct transcription factors (TFs) and histone modifications.…”
Section: Organoids As a Model To Study Regulation Of Expressionmentioning
confidence: 99%
“…The gene ACTL6A was found to regulate the SWI/SNF chromatin remodeling complex as a carcinogen in squamous cell carcinoma to maintain the tumor in an undifferentiated state. Interestingly, uc.291 can act negatively on ACTL6A , reversing the inhibition of differentiation genes mediated by ACTL6A [ 58 ].…”
Section: Pathologymentioning
confidence: 99%
“…Interestingly, both ACTL6A and TP63 are co-amplified in HNSCC, they are also physically co-associated and co-expressed together with other BAF complex subunits co-regulating a key set of relevant targets, including genes encoding components of the Hippo-YAP signaling pathway ( Figure 3a ) [ 64 ]. These findings indicated that p63/BAF function together in a common pathway to counteract differentiation both in normal epithelial progenitor cells and in tumor cells [ 57 , 64 ].…”
Section: Exploiting the P63 Interactome In Epithelial Development And...mentioning
confidence: 99%